Non-Viral Gene Therapy in Trabecular Meshwork Cells to Prevent Fibrosis in Minimally Invasive Glaucoma Surgery - Jinyuan Luo; Greymi Tan; Kai Xin Thong; Konstantinos N. Kafetzis; Neeru Vallabh; Carl M. Sheridan; Yusuke Sato; Hideyoshi Harashima; Aristides D. Tagalakis; Cynthia Yu-Wai-Man (Pharmaceutics, 2022)
The primary cause of failure for minimally invasive glaucoma surgery (MIGS) is fibrosis in the trabecular meshwork (TM) that regulates the outflow of aqueous humour, and no anti-fibrotic drug is available for intraocular use in MIGS. The myocardin-related transcription factor/serum response factor (MRTF/SRF) pathway is a promising anti-fibrotic target. This study aims to utilise a novel lipid nanoparticle (LNP) to deliver MRTF-B siRNA into human TM cells and to compare its effects with those observed in human conjunctival fibroblasts (FF). Two LNP formulations were prepared with and without the targeting peptide c<semantics>Υ</semantics>, and with an siRNA concentration of 50 nM. We examined the biophysical properties and encapsulation efficiencies of the LNPs, and evaluated the effects of MRTF-B silencing on cell viability, key fibrotic genes expression and cell contractility. Both LNP formulations efficiently silenced MRTF-B gene and were non-cytotoxic in TM and FF cells. The presence of c<semantics>Υ</semantics> made the LNPs smaller and more cationic, but had no significant effect on encapsulation efficiency. Both TM and FF cells also showed significantly reduced contractibility after transfection with MRTF-B siRNA LNPs. In TM cells, LNPs with c<semantics>Υ</semantics> achieved a greater decrease in contractility compared to LNPs without c<semantics>Υ</semantics>. In conclusion, we demonstrate that the novel CL4H6-LNPs are able to safely and effectively deliver MRTF-B siRNA into human TM cells. LNPs can serve as a promising non-viral gene therapy to prevent fibrosis in MIGS.